The Middle Turbinate Resection and Its Repercussion in Olfaction with the University of Pennsylvania Smell Identification Test (UPSIT) - Mariano,Fernando Cesar (2018)
Abstract Introduction Nasal obstruction is a common complaint, and, for some, the middle turbinate resection is still a controversial issue among the surgical options due to the possibility of deleterious effects on olfaction. The University of Pennsylvania smell identification test (UPSIT) is considered the gold standard of smell identification tests, but data about it is still incipient in Brazil. Objective To evaluate if the middle turbinectomy has any repercussion on the sense of olfaction by using the UPSIT as an assessment tool. Methods A prospective study performed between 2013 and 2015 with 27 patients who were treated with middle turbinectomy by the same surgeon and tested with the UPSIT pre- and post-surgery, with a minimum interval of 3 months. Results Twenty-five patients completed the study. The mean age was 27.9 years. There was no statistical correlation betweenmiddle turbinectomy and the UPSIT score, or between gender and the UPSIT score. Conclusion There was no clinical repercussion on olfaction from partial middle turbinectomy.